Asset Sell-Offs, Equity Carve-Outs, Spin-Offs or Targeted Stocks : Determinants of Divestiture Decision - Neužilová, Kateřina (2022)
Divestitures are complex transactions which stem from a decision of a company to separate a portion of its assets. They represent a part of portfolio restructuring which is connected with the corporate strategy. Companies undertake divestitures for manifold reasons which can be categorized into strategic, financial and organization. Nevertheless, the determinants of divestiture choice are an under-researched topic, and such this thesis aims to bring more clarity regarding the choice of method: asset sell-off, equity-carve, spin-off, and targeted stock. The empirical part analyses 60 spin-off and equity carve-out. The logit model based on financial synergies, operating performance, financial needs, and riskiness is presented. Regarding implications, price multiples and profitability measures are used to analyse effectiveness of operations and profitability improvements.